The Impact of career motivation, emotional exhuastion on job satisfaction and turnover intention : a study of hotel frontline employees in Malaysia / Mitra Kiany - Kiany, Mitra (2013)
This study develops and tests a model that investigates the effects of career motivation and emotional exhaustion on job satisfaction and turnover intention. Using data from frontline employees in Kuala lumpur Results show that emotional exhaustion is positively related to employee turnover intention and negatively related to job satisfaction. However, the study results demonstrate that extrinsic and intrinsic motivations have significant relationship with intrinsic and extrinsic job satisfaction. Results indicate that emotional exhaustion leads to job dissatisfaction, Results reveal that intrinsic motivation is significantly related to job satisfaction, and turnover intention. In addition, the study results provide empirical support for the negative impact of job satisfaction on employee turnover intention. Discussion and implications of the results are presented in the study